Novel axially-substituted silicon phthalocyanines with pH-modulated fluorescence ON/OFF switching properties - Sahin, Belgin; Ongun, Nerve Zeyrek; Topel, Sevinc Zehra; Gurek, Aye Gul; Atilla, Devrim (World Sci Publ Co Inc, 2019)
Two novel axially-substituted asymmetric silicon (IV) phthalocyanines, the first one substituted with both polyethylene glycol and indomethacin groups (Pc1) and second one substituted with both polyethylene glycol and mefenamic acid groups (Pc2) have been designed and synthesized for the purpose of pH sensing examinations. Their absorption and fluorescence emission-based spectral properties were investigated in chloroform, tetrahydrofuran and toluene. The pH-sensing properties of Pc1 and Pc2 were examined in detail by using UV-vis absorption and fluorescence spectroscopies in tetrahydrofuran. The effects of the substituents on the spectroscopic properties and pH-sensing behavior of these silicon phthalocyanines were revealed. Pc1 didn't show a pH response; however, Pc2 exhibited a signal increase from pH 5.40 to 0.37 (turn on) and a drastic quenching when pH went from 0.37 to 5.40 (turn off). The protonation/deprotonation stage of the NH group of Pc2 presented fluorescence-based on-off type molecular switch properties.
Keywords: silicon phthalocyanine; fluorescence; photocharacterization; pH sensing properties; isosbestic point; ''on-off'' type switches